Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.4067/s0717-95022008000300031
|View full text |Cite
|
Sign up to set email alerts
|

Microarchitectural Adaptations in the Stomach of African Tree Pangolin (Manis tricuspis)

Abstract: The microarchitecture of the pangolin's stomach favouring the high chitinous diet has been less waived into, despite extensive morphological investigations. Histological analysis of the microanatomy will provide powerful tools for interpretation to yield reliable insights. We investigated this by fixing the tissues in 10% formol saline for histological analysis. Serial sections at 5 µ m thickness were subjected to general staining methods for light microscopic study (Haematoxylin and eosin, Van Gieson's and Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
0
14
1
1
Order By: Relevance
“…Currently, reviews on the gastric anatomy of Vietnamese wild pigs indicated that they were very similar in their anatomy to that of the domestic pig [20]. The findings in this study as opposed to the documented reports [1720] showed that at least the gastric morphometry of the Vietnamese wildpigs in Vietnam have not probably undergone any significant change.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…Currently, reviews on the gastric anatomy of Vietnamese wild pigs indicated that they were very similar in their anatomy to that of the domestic pig [20]. The findings in this study as opposed to the documented reports [1720] showed that at least the gastric morphometry of the Vietnamese wildpigs in Vietnam have not probably undergone any significant change.…”
Section: Discussioncontrasting
confidence: 43%
“…The result of stomach dimensions once again demonstrated that the change of physiology of stomach is the consequence of the impermanent in “quantity and quality” of food source [16] and the difference in the location of regression illuminates the dissimilarity degree of adaptation [17]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires us to understand the physiology of pangolin’s digestive system comprehensively. There are some anatomical analysis of pangolin’s digestive system recently (Adeniyi et al 2012; Munyala et al 2011; Ofusori et al 2008), but it is still unknown why pangolin selectively preys on ants and termites. Analyzing pangolin’s digestive enzyme composition and identifying its critical categories may provide us some clues.…”
Section: Lessons From Our Practical Experiencesmentioning
confidence: 99%